1979
DOI: 10.1111/j.1365-2141.1979.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Number of Peripheral Blood Granulocytic Progenitor Cells in Patients with Down's Syndrome

Abstract: The number of granulocytic progenitor cells (colony forming units in culture: CFUc) in the blood of patients with Down's syndrome was found to be reduced by 73.2% when compared to a group of age and sex matched controls. However, the blood CFUc of the Down's syndrome patients and the controls showed similar sensitivity to hydroxyurea which suggests that the low number of progenitor cells in Down's syndrome is not compensated by a marked increase in their cellular proliferation. The colony size distributions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A marked decrease in the number of haematopoietic colony-forming cells has been observed in peripheral blood of DS patients (Standen et al, 1979) and fetal liver of trisomy 16 mouse embryos (Herbst et al, 1982;Epstein et al, 1985). The data presented here show that genedosage of CuZnSOD alone can cause a decrease in haematopoietic colony-forming cells in the bone marrow from adult mice, especially under stress conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A marked decrease in the number of haematopoietic colony-forming cells has been observed in peripheral blood of DS patients (Standen et al, 1979) and fetal liver of trisomy 16 mouse embryos (Herbst et al, 1982;Epstein et al, 1985). The data presented here show that genedosage of CuZnSOD alone can cause a decrease in haematopoietic colony-forming cells in the bone marrow from adult mice, especially under stress conditions.…”
Section: Discussionmentioning
confidence: 98%
“…DS patients suffer from a wide range of symptoms including mental retardation and abnormal external features (Benda, 1969;Epstein, 1986). They also show high susceptibility to infections and have abnormalities in their thymus and bone marrow (Benda, 1969; Levine et al, 1979;Standen et al, 1979;Tolksdorf and Wiedemann, 1981;Ugazio, 1981;Epstein, 1986Epstein, , 1989. Mouse fetuses with trisomy 16, a mouse model for human trisomy 21 (Epstein et al, 1990), also exhibit abnormalities similar to those found in DS; a hypoplastic thymus and a decreased number of haematopoietic progenitor cells in their liver (Epstein et al, 1985(Epstein et al, , 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought to be provoked by stress or by a misdiagnosed viral infection, but the magnitude of the response is such that acute leukemia is diagnosed and the diagnosis is not rectified until the affected child recovers. Other abnormalities include thrombocytopenia, neonatal polycythemia, a reduced number of granulocytic progenitor cells, and abnormalities in the lobe counts of polymorphonuclear leucocytes (Mittwoch 1958, Weinberger and Oleinick 1970, Sigler and Zinkham 1972, Standen et al 1979. The existence of the reversible leukemoid reaction, together with the other abnormalities, suggests that a stemcell defect is associated with the syndrome.…”
Section: Leukemia and Other Cancersmentioning
confidence: 99%
“…Bone marrow was obtained from ribs removed routinely from patients undergoing thoracotomy. Peripheral blood samples from healthy volunteers were separated to produce a mononuclear cell fraction enriched for CFUc (Standen, Philip & Fletcher, 1979). This cell fraction or the bone marrow was used as a source of CFUc (target cells).…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%